Peran Surat Berharga Syariah (SBSN) dalam Pertumbuhan Pembangunan Ekonomi Indonesia: The Role of State Sharia Securities (SBSN) in Indonesia's Economic Development Growth - Natama Harahap, Dea Novika; Melda, Fikahan; Hasibuan, Abdul Nasser (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2025)
This study employs a qualitative method with a library research approach aimed at analyzing the role of sukuk in promoting national economic growth in Indonesia. The data were obtained from secondary sources such as academic literature, journals, books, and relevant research reports. The analysis was conducted theoretically to derive objective and comprehensive conclusions. The findings reveal that national economic growth can be stimulated through the issuance of Islamic bonds or sukuk, which include State Sukuk (Surat Berharga Syariah Negara/SBSN) and corporate sukuk. The issuance of SBSN has contributed significantly to increasing state revenue and financing strategic projects in various sectors such as energy, telecommunications, transportation, agriculture, manufacturing, and housing. Furthermore, sukuk plays a vital role in expanding the Islamic financial market, diversifying the investor base, providing alternative investment instruments, and optimizing the use of state assets and public funds outside the conventional banking system. Therefore, sukuk serves as a strategic instrument in strengthening the national economy based on Sharia principles.